'I will not put this request at the very beginning': Chinese EFL students' perception of pragmatic (in)felicity in English email requests. (2nd February 2019) - Zheng, Qun; Xu, Ying
Abstract : Pragmatic (in)felicity in requests refers to the (in)appropriateness and (im)politeness of one's language use. It has been a great challenge to L2 learners, as they are likely to compose grammatically correct but pragmatically infelicitous requests. Such infelicity could be associated with pragmalinguistic and sociopragmatic factors, yet whether L2 learners are aware of those factors has been underexplored. To understand the effects of power, imposition, and modifications on email perception, we designed a matched guise test for 224 Chinese L2 learners, who were instructed to rate from 1 (very inappropriate/impolite) to 5 (very appropriate/polite) on four email requests (Power±; Imposition±). We found that (1) learners are highly aware of pragmalinguistic factors because they perceive requests mitigated by internal and external modifications as more appropriate and polite (p < .05), (2) learners have limited awareness of power difference as they rank direct form as inappropriate in peer-to-peer interaction, and (3) learners cannot realise fully the sociopragmatic factors involved in high-imposition situations. The awareness of pragmatic (in)felicity among learners seems to be underdeveloped as regards degree of power and imposition. The findings could have some implications in language pedagogy.